Statistical and stochastic feasibility studies of potential liquid organic hydrogen carriers in a membrane reactor for simultaneous hydrogen storage and production: Technical, economic, and environmental aspects. (August 2022) - Byun, Manhee; Choe, Changgwon; Cheon, Seunghyun; Lee, Aejin; Lim, Hankwon
Abstract: With a global trend of transition to the hydrogen-based energy system, the importance of improved systems of hydrogen production and transportation is emphasized. Especially, liquid organic hydrogen carrier is introduced due to its significant advantages when it is employed as a hydrogen energy carrier. In this study, the comprehensive preliminary feasibility study in technical, economic, and environmental aspects for hydrogen production systems using several promising systems of dodecahydro-N-ethycarbazole, Perhydro-dibenzyltoluene, methylcyclohexane, and methanol in a membrane reactor is conducted to investigate its potential to be alternative hydrogen production and transportation. With process simulation using Aspen Plus® based on detailed reaction kinetics for dehydrogenation of each dehydrogenation system and steam reforming of methanol, technical performance in terms of production rate is revealed. In addition, unit hydrogen production costs and key economic parameters for each system at various scales are estimated and compared by itemized cost estimation. Furthermore, realistic uncertainty analysis reflecting detailed distributions of each economic parameter obtained by various regression types of triangular, Epsilon skew normal, Birnbaum-Saunders, and Rayleigh and environmental assessment using SimaPro® are conducted revealing possible ranges of unit hydrogen production cost and carbon dioxide emission rate.